Responses of nitrite-oxidizing bacteria community to excessive nitrogen application and straw incorporation under intensive cultivation. Issue 9 (29th July 2022) - Zhang, Haosu; Liang, Fei; Wang, Yiyao; Wen, Yongkang; Pan, Guangyuan; Jiang, Fangying; Luo, Huaying; Song, He
ABSTRACT: N fertilization and straw incorporation often disturb the soil and may affect nitrite oxidation (NO); however, the underlying mechanism remains unclear. Here, we collected soil samples through a 4-year field experiment including no N fertilization, normal N application, excess N application (EN), and EN plus straw incorporation (ES) treatments. We measured the community composition, abundance, and activity of Nitrobacter -like and Nitrospira -like nitrite-oxidizing bacteria (NOB). N application and straw incorporation significantly enhanced potential NO activity (PNO). PNO was affected by the abundance of Nitrobacter but not Nitrospira and the community compositions of both NOB. With increasing N application rate, Nitrobacter abundance increased from 1.0 to 11.8 × 10 4 copies g −1 dry weight soil, whereas Nitrospira abundance increased initially then subsequently decreased, ranged from 2.1 to 5.2 × 10 6 copies g −1 dry weight soil. Moreover, N application and straw incorporation markedly affected the NOB community composition. Soil pH and organic C were the key factors shaping the NOB community composition. Overall, N fertilization combined with straw incorporation can affect NO by altering the Nitrobacter abundance and NOB community composition. These findings expand our understanding of mechanisms underlying the effects of straw incorporation on nitrification, particularly under N enrichment.